Myosin Vb Mobilizes Recycling Endosomes and AMPA Receptors for Postsynaptic Plasticity - Wang, Zhiping (2008)
Learning-related plasticity at excitatory synapses in the mammalian brain requires the trafficking of AMPA receptors and the growth of dendritic spines. However, the mechanisms that couple plasticity stimuli to the trafficking of postsynaptic cargo are poorly understood. Here we demonstrate that myosin Vb (MyoVb), a Ca(2+)-sensitive motor, conducts spine trafficking during long-term potentiation (LTP) of synaptic strength. Upon activation of NMDA receptors and corresponding Ca(2+) influx, MyoVb associates with recycling endosomes (REs), triggering rapid spine recruitment of endosomes and local exocytosis in spines. Disruption of MyoVb or its interaction with the RE adaptor Rab11-FIP2 abolishes LTP-induced exocytosis from REs and prevents both AMPA receptor insertion and spine growth. Furthermore, induction of tight binding of MyoVb to actin using an acute chemical genetic strategy eradicates LTP in hippocampal slices. Thus, Ca(2+)-activated MyoVb captures and mobilizes of REs for AMPA receptor insertion and spine growth, providing a mechanistic link between the induction and expression of postsynaptic plasticity.